In vitro and in vivo pathogenicity of Plesiomonas shigelloides. - Herrington, D A (1987)
Epidemiologic evidence suggests that Plesiomonas shigelloides is an enteric pathogen. We conducted in vitro, animal, and volunteer studies on P. shigelloides isolates from patients with diarrhea. Five strains gave a negative keratoconjunctivitis reaction in guinea pigs and did not invade HeLa cells. Genetic probes for heat-stable enterotoxins related to those of enterotoxigenic Escherichia coli and for gene sequences common to the invasiveness plasmids of Shigella spp. and enteroinvasive E. coli were negative. Heat-labile enterotoxins were not found when a modified GM1-enzyme-linked immunosorbent assay was used. Rabbits did not develop diarrhea but were transiently colonized when inoculated with up to 10(11) P. shigelloides CFU using the reversible intestinal tie adult rabbit diarrhea model. A very large plasmid (between 118 and 312 megadaltons) was found in all isolates. Strain P012 was cured of its plasmid by novobiocin. This strain, but not its cured derivative, invaded the mucosa of the distal ileum of gnotobiotic piglets given 10(10) CFU. At a lower inoculum (10(9) CFU), strain P012 induced inflammation of the colonic mucosa and diarrhea at day 6. The same isolate was fed to 33 healthy volunteers in doses of 1 X 10(3) to 4 X 10(9) CFU. Thirty-six percent of the volunteers shed the organism, but none became ill. These data are only weakly supportive of a role for P. shigelloides in diarrheal illness and suggest the need for more studies with other strains to better understand its pathogenicity.